SURVEY KEPUASAN ANGGOTA GAPOKTAN TERHADAP PERAN PENGURUS KELOMPOK TANI DI GAMPONG KULAM ARA KECAMATAN MUTIARA TIMUR KABUPATEN PIDIE - Julia, Andria Syah Putra, Nurfadhilah (Jurnal Agroristek, 2020)
This study aims to find out the survey of gapoktan members' satisfaction survey on the role of farmer group members in Gampong Kulam Ara Kecamatan Mutiara Timur. The research started from July 25 until August 15, 2017. The research used descriptive method with population is the whole group of farmer group in Gampong Kulam Ara Sub Mutiara Timur Regency Pidie counted 75 people. Determination of sample of 37 people done by ramdom sampling (random sampling). In this case taken a sample of 37 people for research purposes. The data obtained consist of primary data and secondary data, both qualitative and quantitative data. The analysis used in this research is as follows: P = F / NX100%. The results of this study indicate that the survey of gapoktan members' satisfaction on the role of farmer group members in Gampong Kulam Ara Sub-district of Mutiara Timur Pidie District is included in the good category because it can improve the development of farmer groups in terms of creativity, production and income of farmers through farmer group meetings and the role of executives in the implementation deliberation of farmer groups in the form of participation participation, participation in farmer group meetings and activities, participation in agricultural extension program and group performance capability level in Gampong Kulam Ara Kecamatan Mutiara Timur Kabupaten Pidie.Keywords: Gapoktan, Board Role, Farmer Group